Pulmonary tuberculosis in a child with acute lymphoblastic leukemia-role of empirical therapy - R., Amruta Varshini V.; Nabeela, Ayesha; Jayaraman, Dhaarani; Mahalingam, Harshavardhan; Balasubramanian, Subalakshmi; Scott, Julius X. (International Journal of Contemporary Pediatrics, 2024)
Children with B-cell acute lymphoblastic leukemia (B-ALL) are immunocompromised, making them more prone to various infections. Mycobacteria are not commonly known to cause infections in children with ALL or cancer, and literature detailing tuberculosis (TB) in childhood cancer from high-burden areas is limited. We describe a case of B-ALL presenting with refractory pneumonia, which was finally presumed to be TB. As immunocompromised children typically present with paucibacillary TB, early diagnosis becomes a significant challenge. Paradoxically, the benefits of empirical ATT in this subpopulation are significantly higher than the associated risks such as hepatotoxicity. As TB is a serious infection in immunocompromised children, an empirical ATT regimen can be commenced in the setting of strong clinical suspicion after detailed assessment of the risks associated with concurrent chemotherapy, especially in children hailing from endemic regions.